Motivating Factors Analysis for Halal Certification on the Catering and Restaurant Services in Banyumas Regency - Putri, Astrid Lastani Sukmana; Hidayat, Hety Handayani; Siswantoro, Siswantoro; Wijayanti, Nur (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2023)
Halal certification guarantees that a product is halal for consumption or use, especially for Muslim consumers. However, the number of halal-certified restaurants and catering services in Banyumas Regency, with its predominantly Muslim population, is still minimal. Therefore, this study analyzes the motivational factors for Halal certification in the hospitality industry. The method used is a multiple linear analysis with 9 motivational factors obtained from an in-depth literature study. The regression model formed has an R square value of 48.1%, meaning that 48.1% of the nine factors studied can explain the existing motivation. From the t-test, it is known that 7 factors significantly affect the motivation of restaurant and catering business owners in halal certification, namely customer awareness, religion, the role of halal certificates, increased turnover, halal producer awareness, globalization, and the environment. Based on these results, it is hoped that it can be used by related parties to increase motivation so that there is an acceleration of halal certification to support the food and beverage obligation program in Indonesia in 2024.